The Peer-to-Peer Lending Phenomenon: A Review from Islamic Economic Perspective - Telsy Fratama Dewi Samad; Rosdalina Bukido (Khazanah Sosial, 2022)
This paper aims to describe P2P lending from the viewpoint of Islamic economics as well as enclose the illegal p2p lending phenomenon in Indonesia, and the emergence of p2p lending in Europe and China. This research used a qualitative method, while the data obtained through literature review, and the analysis technic used in this research is descriptive analysis. This paper depicts the issues of p2p lending in global cases and the illegal p2p lending that occurred in Indonesia. The result of this paper disclosed that recently the cases of illegal p2p lending in Indonesia have increased. Albeit the p2p lending provides mashallah concerning to the convenience that it serves to society to obtain loans easily, on the other hand, few perpetrators exploit this media by conducting fraud due to the transaction. Thus, based on the Islamic Economic viewpoint, p2p lending is allowed if only following the principles of Islamic economics and cause no harm to anyone who gets involved in the transaction. Furthermore, Otoritas Jasa Keuangan in Indonesia has guaranteed some p2p lending legal companies which are operating based on Islamic principles. We concluded that, in Islam, it is allowed to conduct p2p lending transactions by using shariah legal p2p lending provided by Otoritas Jasa Keuangan (OJK).